Chemical, microbial and sensory properties of a chestnut and milk ice cream with improved healthy characteristics. Issue 1 (1st January 2020) - Espinoza, Luis A.; Purriños, Laura; Centeno, Juan A.; Carballo, Javier
ABSTRACT: With the aim of revalorization of two productions of economic relevance (milk and chestnuts), a novel ice cream was formulated incorporating milk, chestnut flour and chestnut bits. Using the best sensory valued formula as a basis, eight ice cream formulations were elaborated replacing the ingredients normally used (milk fat, sucrose and carboxymethylcellulose) by healthier ones (olive oil, erythritol + steviol glycosides, and tara ( Caesalpinia spinosa ) gum, respectively). The formulations were analyzed for composition, physicochemical parameters, fatty acid profile, volatile profile, microbiological characteristics and sensory attributes. A general preference of the tasters was observed for the formulations containing sucrose over those made with the hypocaloric sweetener. GRAPHICAL ABSTRACT: